Interpersonal Communication using Symbolic Modeling Techniques in Adolescents - Sari, Dina; Nurihsan, Juntika; Setiawati, Setiawati (Academia Edu Cendekia Indonesia (AEDUCIA), 2023)
Interpersonal communication is very important for individual life. Interpersonal communication plays a role in creating happiness in human life, assisting individual intellectual and social development, forming identity and identity, understanding the reality around individuals, and also for determining individual mental health. Effective interpersonal communication when it has aspects such as openness, empathy, supportive attitude, positive attitude and equality. Symbolic modeling techniques change behavior and add to behavior in order to have good interpersonal communication skills so that counselees can increase self-acceptance, can behave more positively and can understand themselves and others by using literature reviews from several relevant sources.